2011
DOI: 10.1038/nmat3072
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation-based acoustic switching and rectification

Abstract: Experimental configuration. The sensors are placed four sites from the actuator and at the end of the crystal. The sensor located four sites away from the actuator is used to measure the localized vibrations within the vicinity of the defect (without being in direct contact with it, so as to avoid affecting its dynamics). The sensor at the end of the crystal is used to measure the transmission through the crystal. For our rectifier geometry, the bifurcation-based rectification mechanism is only clearly evident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
421
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(427 citation statements)
references
References 26 publications
4
421
1
1
Order By: Relevance
“…Other structures of one-way acoustic devices, such as asymmetric nonlinear bead chains, have been demonstrated thereafter [23]. By introducing nonlinear active electric circuits, with incoherent amplification, into the resonant unit cells in acoustic metamaterials, one can realize a nonreciprocal acoustic metamaterial with a large contrast ratio [24].…”
Section: Scattering Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other structures of one-way acoustic devices, such as asymmetric nonlinear bead chains, have been demonstrated thereafter [23]. By introducing nonlinear active electric circuits, with incoherent amplification, into the resonant unit cells in acoustic metamaterials, one can realize a nonreciprocal acoustic metamaterial with a large contrast ratio [24].…”
Section: Scattering Propertiesmentioning
confidence: 99%
“…Recent advancements in man-made materials ("metamaterials") have resulted in intriguing achievements in acoustic and phononic transport manipulation [1]. These discoveries include dynamic negative density and a bulk modulus [2][3][4][5][6][7][8], subwavelength imaging [9][10][11], acoustic and surface wave cloaking [12][13][14][15], a phononic band gap [16,17], extraordinary acoustic transmission [18,19], Anderson localization [20], and asymmetric transmission [21][22][23][24][25]. These works, so far, are based on the modulation of the real part of the acoustic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Large acoustic isolation has been obtained using option (i) in a non-linear medium paired with a frequency selective mirror [8,9], or with the help of nonlinear acoustic inclusions [10]; however, all these nonlinear solutions typically introduce severe signal distortions and only work for large acoustic intensities. According to the Casimir-Onsager principle of microscopic reversibility [11], linear isolation is possible if the system is biased with an odd-vector upon time reversal, just like the static magnetic field in the case of the Faraday isolator [option (ii)].…”
Section: Introductionmentioning
confidence: 99%
“…We have found that 1D homogeneous GNS lattices 21 support the formation and propagation of weakly dissipative and highly localized solitary wave at room temperature, while 1D diatomic GNS lattices have a good tuning ability of transmittance and wave speed due to the phenomenon of nonlinear resonances.…”
Section: Discussionmentioning
confidence: 97%